(untitled) (PANGEEA, 2025)
ABSTRACT: Sebes City is located at the intersection of two major roads. From the highway Bucharest-Arad-Sibiu, in Sebes emerges another European road, on direction Cluj-Oradea. All the cars coming from the south of Romania and the Balkan Peninsula and head toward Central and Western Europe pass through this city that has no beltway. For this reason, the exhaust gas air pollution is a serious problem of residents of this city. Key words: intersection of major roads, exhaust gas, air pollution.